2022
DOI: 10.3390/agronomy12020489
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Hyperspectral Vegetation Indices for Monitoring Yield and Physiological Response in Sweet Maize under Different Water and Nitrogen Availability

Abstract: This study used hyperspectral reflectance data to evaluate the crop physiological parameters of sweet maize. Principal component analysis (PCA) was applied to identify the wavelengths that primarily contributed to each selected PC. Correlation analysis and multiple linear regression, with a stepwise algorithm, were used to select the best-performing vegetation indices (VIs) for monitoring the yield and physiological response of sweet maize grown under different water and nitrogen availability. The spectral ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 109 publications
1
9
0
Order By: Relevance
“…The sensitive spectral indices of this study were ρ nir , H 500nm , H 675nm , F 710nm , λ 710nm , S 730nm , and λ 730nm due to the influence of salinized soil. Hyperspectral estimation of physiological parameters of sweet corn and other crops showed that the chlorophyll absorption reflectance index (CARI), double difference index (DD), red edge inflection point (REIP), and chlorophyll red edge (CIred-edge) were good predictors of the physiological parameters, confirming the key role of the red edge spectral region [41]. Compared with the above study, the spectral index was not constructed in this study.…”
Section: Effects Of the Nitrogen Application Rate On The Spectral Cha...mentioning
confidence: 62%
“…The sensitive spectral indices of this study were ρ nir , H 500nm , H 675nm , F 710nm , λ 710nm , S 730nm , and λ 730nm due to the influence of salinized soil. Hyperspectral estimation of physiological parameters of sweet corn and other crops showed that the chlorophyll absorption reflectance index (CARI), double difference index (DD), red edge inflection point (REIP), and chlorophyll red edge (CIred-edge) were good predictors of the physiological parameters, confirming the key role of the red edge spectral region [41]. Compared with the above study, the spectral index was not constructed in this study.…”
Section: Effects Of the Nitrogen Application Rate On The Spectral Cha...mentioning
confidence: 62%
“…It has also been employed for the estimation of characteristics such as canopy coverage, leaf area index and leaf chlorophyll content [39]. The TCARI index has been used to monitor the yield and physiological response of sweet corn [40] because it is sensitive to leaf chlorophyll content [41]. It has also been found that it can be used to estimate plant nutrition with model variance values up to 0.83% [42].…”
Section: Discussionmentioning
confidence: 99%
“…DD, REIP, and CI red-edge , belonging to the red-edge group VIs, were the best predictors of physiological and yield parameters at the mid-season stage of sweet maize crop. The differences among water supplies and nitrogen treatments are mainly related to chlorophyll content [66].…”
Section: Rgb and Hyperspectral Vegetation Indices For Estimating Maiz...mentioning
confidence: 99%